Memahami Budaya Konci Negeri di Desa Waai dari Perspektif Eko-Teologi - Margaretha Martha Anace Apituley; Monike Hukubun (Program Pascasarjana UKIM, 2024)
Ecological damage has become a fact of life. One of the local wisdom lived by the people of the village of Waai-Central Maluku to overcome this is the konci negeri culture. This study aims to analyze the konci negeri culture in the village of Waai through an eco-theological perspective and examine the relevance of the meaning of the konci negeri culture in the effort to develop a model for preserving the ecological environment in Maluku. This study used a qualitative research method with field observations, interviews, and FGD as instruments. Based on the research, it is known that the konci negeri is an attempt by the people to avoid various threats of damage to the whole country. Even these stages involve God who is believed to be the giver and preserver of life, as well as ancestors who are understood as parents who come from God and aim to protect the entire Waai.